Participatory budget in metropolies as instrument of direct democracy in public management: experience of Poland and Ukraine - Kudłacz, Michał; Zhebchuk, Roman (Journal of Public Governance, 2019)
Objectives: In the article a comparative research of the participatory budgeting systems at the local level in Poland and Ukraine was carried out. Research Design & Methods: The objects of the study were ten cities of the specified states (five from each country). In the case studies, systemic analysis of legislations of Poland and Ukraine in public finance sphere connected with participatory budgeting were used as well as quantitative analyses of budget resources directed at supporting participatory budget. Using this approach gave us the opportunity for complex research of participatory budgeting mechanism in both countries. Findings: As a result of the research, the peculiarities (differences) of the practice of using participatory budgets as tools of direct democracy at the Ukrainian and Polish cities’ level were specified. On this basis, the authors outlined obstacles for the efficient use of participatory budgets based on the experience of the two countries, formulated guidelines and standards in compliance with which it would be possible to implement quality participatory budgeting into practices of the cities’ public administration. Implications / Recommendations: This article indicates the need to conduct analyzes of participatory budgets to draw conclusions and effectively use this tool in the future. Contribution / Value Added: This research builds knowledge about participatory budgeting by analysing the use of this instrument of direct democracy in two different countries (Poland and Ukraine), which are at different level of EU integration an may help effectively plan and implement participatory budgeting in different national contexts.